2023
DOI: 10.1109/access.2023.3256091
|View full text |Cite
|
Sign up to set email alerts
|

A New Integrated Risk-Assessment Model for Minimizing Human-Machine Error Consequences in a Preventive Maintenance System

Abstract: In this paper, a risk-assessment model for minimizing human-machine error consequences during the implementation of preventive maintenance tasks has developed. The developed model aimed to find the optimal preventive maintenance interval (PMI) and corresponding minimum risk consequences costs per unit of time. Based on expert judgment, a human error probability (HEP) model was developed using the success likelihood index methodology (SLIM). In addition, we developed a system failure probability (SFP) model bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Iraj et al [25] reported that factors affecting HEs in a mining process design are caused by individual factors (lack of knowledge and experience), task factors (multitasking and workload), organizational factors (poor management and training), and environmental factors (inadequate lighting, noise, and poor air quality). Noman et al [26] have studied some factors affecting inspection and maintenance errors, such as unclear instructions and procedures, stress, task complexity, and lack of experience and training, in addition to other work environmental factors such as noise, lighting, etc., Yaniel et al [27] analyzed human errors in a complex manual assembly line and identified 31 factors that caused those errors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Iraj et al [25] reported that factors affecting HEs in a mining process design are caused by individual factors (lack of knowledge and experience), task factors (multitasking and workload), organizational factors (poor management and training), and environmental factors (inadequate lighting, noise, and poor air quality). Noman et al [26] have studied some factors affecting inspection and maintenance errors, such as unclear instructions and procedures, stress, task complexity, and lack of experience and training, in addition to other work environmental factors such as noise, lighting, etc., Yaniel et al [27] analyzed human errors in a complex manual assembly line and identified 31 factors that caused those errors.…”
Section: Literature Reviewmentioning
confidence: 99%